Tasawuf Sebagai Terapi Menemukan Makna Spiritual dalam Hidup Modern - Syauqi, Muhammad (Ameena Journal, 2023)
Sufism in the modern era should reclaim its original role as a method to shape individuals who draw closer to God, creating superior beings. It serves as a path that strengthens the connection between humans, God, and the surrounding society, aiming to achieve a balance between worldly and spiritual life. This balance is considered the key to happiness both in this world and the hereafter. Therefore, the presence of Sufism in the modern world is crucial to guide individuals in maintaining their longing for God. This study is conducted through library research, revealing that Sufism, as a religious science, addresses moral and behavioral aspects within Islam. It also emphasizes the role of Sufism as therapy or healing in the context of modern society influenced by materialism and individualism. Omar Alishah is acknowledged as the proponent of an Islamic method to address mental disturbances through the Sufi tradition. Furthermore, the study highlights the role of Sufism in modern society, recognizing the need for spiritual guidance in facing the negative impacts of materialism. It views Sufism as a magnet with significant potential to preserve personal integrity and provide a moral foundation in the evolving business and industrial landscape. Thus, this study indicates that Sufism remains relevant as a spiritual therapy and moral guide in addressing contemporary societal challenges.